Intra-amniotic inflammation induces preterm birth by activating the NLRP3 inflammasome. Issue 5 (24th December 2018) - Faro, Jonathan; Romero, Roberto; Schwenkel, George; Garcia-Flores, Valeria; Arenas-Hernandez, Marcia; Leng, Yaozhu; Xu, Yi; Miller, Derek; Hassan, Sonia S; Gomez-Lopez, Nardhy
Abstract: Intra-amniotic inflammation is strongly associated with spontaneous preterm labor and birth, the leading cause of perinatal mortality and morbidity worldwide. Previous studies have suggested a role for the NLRP3 (NLR family pyrin domain-containing protein 3) inflammasome in the mechanisms that lead to preterm labor and birth. However, a causal link between the NLRP3 inflammasome and preterm labor/birth induced by intra-amniotic inflammation has not been established. Herein, using an animal model of lipopolysaccharide-induced intra-amniotic inflammation (IAI), we demonstrated that there was priming of the NLRP3 inflammasome (1) at the transcriptional level, indicated by enhanced mRNA expression of inflammasome-related genes ( Nlrp3, Casp1, Il1b ); and (2) at the protein level, indicated by greater protein concentrations of NLRP3, in both the fetal membranes and decidua basalis prior to preterm birth. Additionally, we showed that there was canonical activation of the NLRP3 inflammasome in the fetal membranes, but not in the decidua basalis, prior to IAI-induced preterm birth as evidenced by increased protein levels of active caspase-1. Protein concentrations of released IL1β were also increased in both the fetal membranes and decidua basalis, as well as in the amniotic fluid, prior to IAI-induced preterm birth. Finally, using the specific NLRP3 inhibitor, MCC950, we showed that in vivo inhibition of the NLRP3 inflammasome reduced IAI-induced preterm birth and neonatal mortality. Collectively, these results provide a causal link between NLRP3 inflammasome activation and spontaneous preterm labor and birth in the context of intra-amniotic inflammation. We also showed that, by targeting the NLRP3 inflammasome, adverse pregnancy and neonatal outcomes can be significantly reduced. Abstract : Intra-amniotic inflammation induces the activation of the NLRP3 inflammasome in the fetal membranes and decidua basalis prior to preterm birth, which is significantly reduced by inhibiting such a pathway.